디젤 분사방식에 따른 이종연료 엔진의 성능 및 배기 분석 - 박현욱; Hyunwook Park; 이준순; Junsun Lee; 오승묵; Seungmook Oh; 김창업; Changup Kim; 이용규; Yonggyu Lee; 장형준; Hyungjoon Jang (한국분무공학회지, 2022)
Performance and emissions with different diesel injection methods were analyzed in a natural gas-diesel, dual-fuel engine under low-load conditions. Natural gas was supplied to intake port during the intake stoke to form a natural gas-air premixed mixture for all methods. Diesel was injected directly into the cylinder during the compression stroke in three ways: early injections, late injections, and a combination of early and late injections. The early injections had the highest thermal efficiency among the three methods owing to its highest combustion efficiency. The wide dispersion of diesel before the combustion initiation also allowed superior emissions characteristics.